Principal's Strategy in Improving the Character of Students Through Religious Activities at Islamic High School Malang - Bayu Akbar P, Muhammad; Sulistiani, Ikah Ratih; Wiyono, Dwi Fitri (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the principal's leadership strategy in improving the religious character of students through religious activities at SMA Islam Malang. This study uses a qualitative approach with a case study design, where data is collected through interviews, observations, and documentation, then validated using triangulation of sources and techniques. The results of the study show that school principals implement three main strategies, namely exemplification through direct involvement in religious activities, empowerment of teachers and students in the planning and implementation of religious programs, and routine evaluation of the implementation of religious activities. The strategy has been proven to increase students' discipline, participation, and spiritual motivation, although obstacles such as lack of discipline among some students and limited facilities are still found. The findings of this study confirm that value-based and exemplary leadership has an important role in shaping the religious character of students and contributing to the development of character education practices in schools.